Graphitic Carbon Nitride Induced Micro‐Electric Field for Dendrite‐Free Lithium Metal Anodes. Issue 7 (11th January 2019) - Lu, Ziyang; Liang, Qinghua; Wang, Bo; Tao, Ying; Zhao, Yufeng; Lv, Wei; Liu, Donghai; Zhang, Chen; Weng, Zhe; Liang, Jiachen; Li, Huan; Yang, Quan‐Hong
Abstract: Uncontrolled dendrites resulting from nonuniform lithium (Li) nucleation/growth and Li volume expansion during charging cause serious safety problems for Li anode‐based batteries. Here the coating of nickel foam with graphitic carbon nitride (g‐C3 N4 ) to have a 3D current collector (g‐C3 N4 @Ni foam) for dendrite‐free Li metal anodes is reported. The lithiophilic g‐C3 N4 coupled with the 3D framework is demonstrated to be highly effective for promoting the uniform deposition of Li and suppressing the formation of dendrites. Both density functional theory calculations and experimental studies indicate the formation of a micro‐electric field resulting from the tri‐s‐triazine units of g‐C3 N4, which induces numerous Li nuclei during the initial nucleation stage, effectively guiding the following Li growth on the 3D Ni foam to be well distributed. Furthermore, the 3D porous framework is favorable for absorbing any volume change and stabilizing the solid–electrolyte interphase layer during repeated Li plating/stripping. As such, a Li metal anode based on the g‐C3 N4 @Ni foam has a remarkable electrochemical performance with a high Coulombic efficiency (98% retention after 300 cycles), an ultralong lifespan up to 900 h, as well as a low overpotential (<15 mV at 1.0 mA cm −2 ) at a Li deposition of 9.0 mA h cm −2 . Abstract : Graphitic carbon nitride (g‐C3 N4 )‐coated nickel foam is demonstrated to be highly effective for promoting uniform lithium deposition . The unique micro‐electric field at the tri‐s‐triazine units of g‐C3 N4 induces numerous Li nuclei at initial nucleation stage and, subsequently, these Li nuclei guide well‐distributed Li plating on 3D Ni foam.